2013
DOI: 10.7314/apjcp.2013.14.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Helicobacter Pylori Infection, Results from a Developing Country-Pakistan

Abstract: Background: It is known that blood group antigens are related to the development of peptic ulcer and gastric carcinoma. Infections due to H. pylori are most widespread among the developing regions due to poor standard of public health. This study sought to determine the association of H. pylori with ABO blood groups, age, gender, and smoking status among inpatients at a public sector hospital in Karachi. Materials and Methods: A cross-sectional study was conducted at endoscopy suite at a public sector hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 14 publications
(27 reference statements)
6
16
3
Order By: Relevance
“…This increase in prevalence with age is attributed to annual increase in the rate of infection (Goodman et al, 1996) and birth cohort effect (Banatvala et al,1993 Alvarado-Esquivel, 2013;Dirji et al, 2013). On the other hand, Alizadeh et al (2009) reported that the prevalence of H. pylori was higher in females than males, while Valliani et al (2013) found out that the prevalence was higher in males than females. In this study the prevalence of H. pylori was slightly higher in females than males.…”
Section: Discussionmentioning
confidence: 89%
“…This increase in prevalence with age is attributed to annual increase in the rate of infection (Goodman et al, 1996) and birth cohort effect (Banatvala et al,1993 Alvarado-Esquivel, 2013;Dirji et al, 2013). On the other hand, Alizadeh et al (2009) reported that the prevalence of H. pylori was higher in females than males, while Valliani et al (2013) found out that the prevalence was higher in males than females. In this study the prevalence of H. pylori was slightly higher in females than males.…”
Section: Discussionmentioning
confidence: 89%
“…It has been postulated that TF has a role in adhesion and metastasis through tumor-endothelial cell interactions, which is the key role in cancer metastasis [57]. Many Gramnegative organisms carry TF antigen, and due to antigenic similarity of TF to A antigen, blood Group A individuals have the least aggressive humoral immune response against the TF than Group O individuals, so it might be readily confused by the immune system of blood Group A individuals [11], and hence, blood Group O is less susceptible to cancer or have less aggressive disease.…”
Section: Resultsmentioning
confidence: 99%
“…Those patients are characterized by acid hyposecretion and low serum pepsinogen level [10]. On the other hand, PUD patients carrying blood Group O are prone to have persistent colonization of H. pylori [11] flowing the expression of Lewis antigens (Leb) in gastric mucosa which act as a receptor for bacterial adhesion [12,13], expression of H-antigen on the gastroduodenal cells, acting as a receptor for H. pylori [13][14][15], the expression of blood group antigen b-binding adhesion (babA) on the outer membrane of H. pylori [16], and cagA-positive virulent strain H. pylori which colonizes in both the corpus and antrum [17,18]. Moreover, patients with blood Group O phenotype stimulate a higher inflammatory responses to H. pylori with higher levels of lymphocyte infiltration in the gastrointestinal mucosa [19] and have low level of Von Willebrand factor (VWF) [20], high frequency of secretor status [19], and high gastric acidity which reduces antibiotic therapy efficacy [21].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of Helicobacter pylori (H. pylori) in 1983 is considered one of the most important breakthroughs in the modern gastroenterology [1,2]. H. pylori is one of the most important public health problems [3]. Globally, it was estimated during 2015 that 4.4 billion persons were infected with H. pylori [1], and such a prevalence of over 50% of the world's population makes it the commonest global chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori bacterium is one of the commonest microbiological agents globally, [3,4] and in the Kingdom of Saudi Arabia (KSA). A recent study in KSA revealed that H. pylori was highly prevalent among Saudi children from Jeddah and Riyadh [5].…”
Section: Introductionmentioning
confidence: 99%